Health belief model and social media engagement: A cross-national study of health promotion strategies against COVID-19 in 2020 - Mao, Zhifei; Wang, Di; Zheng, Shanshan (Frontiers in Public Health, 2023)
Background Using the Health Belief Model (HBM), this study analyzed tweets related to COVID-19 published by national health departments of the United States, the South Korea, the United Kingdom, Japan, Germany, and India to explore their differences in (1) the health measures against COVID-19, (2) the health promotion strategies, (3) the social media engagements that those measures and strategies have triggered. Method We conducted a content analysis with 1,200 randomly selected COVID-19-related tweets from six national health departments' Twitter accounts from 1 January 2020 to 31 December 2020. We coded the six HBM constructs and 21 sub-themes of the HBM constructs for each tweet. Results Results showed that all six HBM constructs were used in the full sample. The most commonly used HBM construct was cues to action, followed by susceptibility, benefits, self-efficacy, severity, and barriers. All the HBM constructs were positively related to Twitter engagement variables except barriers. Further analysis illustrated that people from the six countries responded differently to the HBM constructs and the HBM sub-themes. Twitter users in Germany, India, the U.S., and Japan positively reacted to the clear directions of “what to do against COVID-19” (cues to action), while Twitter users in the U.S. and Japan were also eager to know the justifications for such directions (benefits); people in South Korea and the U.K. were mainly seeking a diagnosis of the severity and susceptibility of COVID-19, instead of health measures, of COVID-19 in the year 2020. Conclusions This study showed the use of HBM constructs is generally effective in inducing Twitter engagement. The further comparison illustrated a homogenization in the promotion strategies that the health departments implemented and the health measures they promoted, yet responses to such promotions varied across nations. This study broadened the scope of HBM applications from predicting health behaviors in surveys to guiding the design of health promotion messages online.